Radiation-Thermal Effects and Processes in Inorganic Materials : 13th International Conference "Radiation-Thermal Effects and Processes in Inorganic Materials" (13th RTEP-2017) : selected, peer reviewed papers from the XIII International Conference "Radiation-Thermal Effects and Processes in Inorganic Materials" October 9-14, 2017, Tomsk, Russia - Gyngazov, Sergey (Key engineering materials, 2018)
This issue of the journal is dedicated to the results of scientific and applied research presented at the XIII International Conference "Radiation-Thermal Effects and Processes in Inorganic Materials" (October 9-14, 2017, Tomsk, Russia). The selected papers cover the actual scientific problems in the area of physical and chemical phenomena in inorganic materials in radiation, electrical and thermal fields and modification of the structure and properties of inorganic materials by methods of radiation-thermal effects. Polymers, Composites, Steel, Alloys, Ceramics, Plasma Technologies, Films Deposition, Radiation-Thermal Effects, Ion Irradiation, Inorganic Materials, Materials Properties, Photochemistry, Biochemistry, Environmental Engineering, Technologies of Food Processing Materials Science